Hyperglycemic Crisis in Uncontrolled Diabetes Mellitus Type 2 Presenting as Breathlessness - Putu Intan Kusuma Wardani; Christina Pretaliana; Henry Theo Prawira Sugitto; Eqen Desmonta; Kevin Hersan; Vannesa Shelly; Varda Natasya Hutapea; Fadhilla Liefya Zahraisha; Jeffrey Christian Mahardhika; Nafthalena; Theresia Monica Rahardjo (Medical Clinical Update, 2022)
Background Hyperglycemic crisis is emergency caused by metabolic problems due to uncontrolled diabetes mellitus. Hyperglycemic crisis consists of Hyperosmolar Hyperglycemic State (HHS) and Diabetic Ketoacidosis. Both are caused by relative or absolute deficiency of insulin; deficiency of insulin could be caused by type 1 and type 2 diabetes. Case presentation A 46-year-old woman came to the emergency room of Unggul Karsa Medika Hospital presenting with breathlessness which had occurred for a week. Her breathlessness was more severe on the day she presented to the emergency room. One week before, she went to a clinic nearby because of epigastric pain, but after returning home she felt breathless. After a few days, her breathlessness started to worsen, so she decided to go to emergency room. The patient had severe acidosis and high blood glucose. Hyperglycemia protocol of rehydration and insulin drip intravenously, accompanied by sodium bicarbonate and potassium chloride were given. Mechanical ventilation was used. The patient was healed and discharged safely after 9 days of hospitalization. Conclusion Hyperglycemic crisis is one of true emergency that can lead to mortality, thus prompt diagnosis and treatment should be done. It is important for clinicians to differ between HHS and DKA. HHS is caused by the relative or absolute deficiency of insulin while DKA is characterized by absolute insulin deficiency which prevents the body from metabolizing carbohydrates and results in severe hyperglycemia. In DKA and HHS the main goal of therapy is to rehydrate, correct hyperglycemia, and to correct electrolyte imbalances.